ANALISIS DAN PERANCANGAN LOAD BALANCING MENGGUNAKAN METODE ROUND ROBIN DAN CARP (STUDI KASUS PADA ASTRIDO GROUP) - Ahmad Rais Ruly (LPPM Universitas Bina Sarana Informatika, 2014)
Proxy can be understood as a third party that stands in the middle between the two parties that are interconnected and function as an intermediary , such that the first party and second party not directly related , but each is associated with an intermediary proxy . Proxy technique is a standard technique for internet access together - together by multiple computers at once in a Local Area Network ( LAN ) through a modem or channel of communication . The term proxy itself widely known and used diplomatic world . In a simple proxy is a person ( institution ) who acts as an intermediary or on behalf of another person ( agency / other countries ) . When many requests from users , the server will be overwhelmed at having to perform service to the user's process . Load balancing or load balancing in the network is very important when the scale in the larger computer networks as well as existing data traffic in computer networks increasingly high . Load Balancing service possible accessing resources in a distributed network to some other host that is not centralized so that the performance of the computer network as a whole can be stabilized